Organization of Teaching of Cadets Professionally Oriented English Monologue Speaking - Nesyn, Yuliya (Pedagogical Discourse, 2013)
The article gives the main recommendations concerning organization of teaching cadets professionally oriented English monologue speaking. The results of the experimental teaching showed that recommendations can improve teaching cadets professionally oriented English monologue speaking. The given recommendations concern organizational forms of teaching cadets, term of teaching cadets professionally oriented English monologue speaking, stages of teaching cadets professionally oriented English monologue speaking, optimal classroom desk arrangement, performance regimes in the class, level of teacher control, error correction, cadets assessment of each other and so on.